Research on the IP alias resolution technology - Zhanfeng WANG; Guang CHENG; Chao HU; Han LI; Nianfeng WENG; Huaping CAO (Tongxin xuebao)
IP alias resolution,the procedure of identifying IP addresses belonging to the same router,is a critical step in Internet topology inference.It can convert the Internet logical topology into physical topology,and bridge the gap between the virtual world and real world.First the concept of IP alias resolution was introduced and the classical IP alias relationships were analyzed.Then the IPv4 alias resolution algorithms and the IPv6 alias resolution algorithms were discussed in detail separately.Finally,through the comprehensive analysis and comparison of all the algorithms,the research directions in the future especially in IPv6 alias resolution were pointed out in three folds such as alias target set selection,fingerprint selection and inference methods.